Convergent and Divergent Mechanisms of Epileptogenesis in mTORopathies - Lena H. Nguyen; Lena H. Nguyen; Angélique Bordey; Angélique Bordey (Frontiers Media S.A., 2021)
Hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) due to mutations in genes along the PI3K-mTOR pathway and the GATOR1 complex causes a spectrum of neurodevelopmental disorders (termed mTORopathies) associated with malformation of cortical development and intractable epilepsy. Despite these gene variants' converging impact on mTORC1 activity, emerging findings suggest that these variants contribute to epilepsy through both mTORC1-dependent and -independent mechanisms. Here, we review the literature on in utero electroporation-based animal models of mTORopathies, which recapitulate the brain mosaic pattern of mTORC1 hyperactivity, and compare the effects of distinct PI3K-mTOR pathway and GATOR1 complex gene variants on cortical development and epilepsy. We report the outcomes on cortical pyramidal neuronal placement, morphology, and electrophysiological phenotypes, and discuss some of the converging and diverging mechanisms responsible for these alterations and their contribution to epileptogenesis. We also discuss potential therapeutic strategies for epilepsy, beyond mTORC1 inhibition with rapamycin or everolimus, that could offer personalized medicine based on the gene variant.